1975
DOI: 10.1111/j.1365-4362.1975.tb04289.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Versicolor Hypopigmentation: Histochemical and Therapeutic Studies

Abstract: One hundred and thirty-four patients with tinea versicolor were divided into 3 treatment groups: (1) 30% sodium thiosulfate application, (2) 30% sodium thiosulfate application plus ultraviolet light, and (3) 30% sodium thiosulfate application, ultraviolet light, and meladinine tablets (amoidin 0.01 g and amidin 0.005 g). Analysis of the 79 patients who completed the 6-week study showed no statistical difference. Therefore, topical treatment should be instituted as quickly as possible to prevent pigmentary chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
1
18
0
2
Order By: Relevance
“…In H-E-stained sections, besides fungi in the upper part of the stratum corneum, a pcrivascular infiltrate of lymphocytes and granulocytes was seen iH ~ln' upper dermis. This has been shown previously (5,7,17). Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…In H-E-stained sections, besides fungi in the upper part of the stratum corneum, a pcrivascular infiltrate of lymphocytes and granulocytes was seen iH ~ln' upper dermis. This has been shown previously (5,7,17). Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…This inflammation has been thought to contribute to the coloration of the paler hyperpigmented lesions. The perivascular infiltrate contains lymphocytes, plasma cells and histiocytes, 36,49 which are involved in the immune reaction. Malassezia furfur can also activate complement by both the classical and alternative pathways, 13 contributing to the inflammation often seen in pityriasis versicolor patients.…”
Section: Immune Response To Malassezia In Pityriasis Versicolormentioning
confidence: 99%
“…Several theories have been proposed to explain hypopigmentation, including the filtering of UV light by the growth of the organism in the skin (14), a block in the transfer of melanosomes to keratinocytes (14,89,121,153,208), and the inhibition of melanin production by azelaic acid (180,302) or by lipoxygenase (304). Other groups have suggested that the hyperpigmentation of lesions was due to inflammation (116,153), increased skin thickness, or larger numbers of organisms in the skin (153).…”
Section: Pityriasis Versicolormentioning
confidence: 99%